Public deaths and negotiation opportunities: Cats, dogs and people in COVID China - Zong, Chenyu (The Australian journal of anthropology, 2025)
Under the extraordinary circumstances of COVID, some health workers in China ruthlessly killed pet dogs and cats, which were thought to be dangerous virus vectors. Heart-wrenching images circulated widely on social media, where some social media commentators used them as a basis to make accusations about generalised Chinese brutality towards animals. At the other end of the spectrum, my Chinese interlocutors went to extraordinary lengths to care for their pets and those of others during extended and very strict lockdown periods. In this paper, I draw on the idea of a reciprocal gaze held between animals and humans that begets mutual respect and commingled being. I use this key idea to explore how Chinese citizens living in COVID lockdowns navigated the regulations regarding animal lives and reconciled the state's protection of humans from the virus with their own desires to protect their pets.